P275 Prevalence and Strain Typing Results Of Gram-negative Emerging Bacterial Pathogens in Patients Attending a Large UK Adult CF Centre. (12th November 2015) - Green, HD; Bright-Thomas, R; Kenna, D; Jones, AM
Abstract : Introduction: In recent years Gram-negative bacterial emerging pathogens (EP) have been noted to infect the airways of patients with CF. Prevalence of EP is increasing but much remains unknown. This study aimed to determine prevalence of EP at a large adult UK centre and whether these organisms may be capable of cross infection. Methods: Prevalence of Burkhoderia multivorans ; Stenotrophomonas maltophilia and Achromobacter ; Ralstonia and Pandoraea species was calculated in October 2013 and 2014. Strain typing was performed on EP isolated from patients from January 2008 to present using pulsed-field gel electrophoresis following restriction with Xba I. Epidemiology of patients with shared strains was analysed by reviewing patient addresses, outpatient appointments, admissions, paediatric centres and asking patients about their social behaviours. Results: In October 2013, 358 patients had at least 1 sputum culture result in the previous 12 months and were included in the prevalence calculation. This increased to 368 patients in October 2014. Prevalence of most EP increased between 2013 and 2014. EP prevalence in 2014 ranged from 1.9% ( Ralstonia species) to 6.2% ( B. multivorans ) (Table 1 ). 96 patients had ≥ 1 isolation of an EP between January 2008 and July 2015. Of these, 20 (21%) have had >2 strains of EP isolated from their sputum within that timeframe. To date, strain typing has been performed on 97 of 115 identified isolates from 96 patients. Shared strains of EP in unrelated patients with epidemiological connexions other than place of home residence were found in cases of infection with Achromobacter, Ralstonia and Pandoraea species. Shared strains of B. multivorans were found in a sibling pair, an unrelated pair with no temporal overlap in positive cultures and in 4 patients with no clear opportunities for cross infection to have occurred. Conclusions: Prevalence of EP is low at our centre but is slowly increasing. History of EP infection appears to be a risk factor for infection with other EPs. Shared strains of Achromobacter, Ralstonia and Pandoraea species have been identified in our centre in patients with epidemiological connexions. Numbers are too small to establish whether cross infection or a common environmental source is responsible.